THE ROLE OF THE OCCUPATIONAL NURSE IN LABOR PRACTICES IN THE VARIOUS OCCUPATIONAL LEVELS - Sobral Silva do Nascimento, Andresa (Health and Society, 2023)
Objective: To know how nursing care is carried out in the various sectors of occupational health care. Methods: this is an integrative literature review, based on the search for scientific articles in the databases Scientific Electronic Library Online (Scielo), Latin American and Caribbean Literature in Health Science (Lilacs); virtual health library (VHL), with the search for data between the years 2014 to 2021. Results: 2,233 articles were found and only two remained, where they identified that the nurse has a fundamental role in the prevention and help in cases of occupational diseases. Conclusion: We conclude our bibliographical review by reporting a great difficulty in research on the subject, as there are few published literature on the subject.